2015
DOI: 10.1016/j.ebiom.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin Synergizes with Cationic Antimicrobial Peptides to Exert Bactericidal and Therapeutic Activity Against Highly Multidrug-Resistant Gram-Negative Bacterial Pathogens

Abstract: Antibiotic resistance poses an increasingly grave threat to the public health. Of pressing concern, rapid spread of carbapenem-resistance among multidrug-resistant (MDR) Gram-negative rods (GNR) is associated with few treatment options and high mortality rates. Current antibiotic susceptibility testing guiding patient management is performed in a standardized manner, identifying minimum inhibitory concentrations (MIC) in bacteriologic media, but ignoring host immune factors. Lacking activity in standard MIC te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
233
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(242 citation statements)
references
References 44 publications
6
233
0
3
Order By: Relevance
“…Yet, we found that when combined with colistin it did exhibit an activity against drug resistant acinetobacter although this combination only produced a synergistic effect on 30% of our isolates, similarly a small number of studies demonstrated the same activity for AZM against Gram negative bacilli with no explanation or suggestion about the mechanism of synergy [31] [32]. Until Lin et al 2012 tested this combination in eukaryotic cell media and in vivo murine models of infection and concluded that AZM entry and activity is synergistically enhanced when the bacterial outer membrane was disrupted by colistin [11]. Buyck et al, 2012 demonstrated that a mutation of the oprM efflux pump system in P. aeruginosa lead to an increased AZM susceptibility, and on entry AZM reduced oprM gene expression and protein synthesis, further enhancing the entry of AZM in eukaryotic media and in synergy with colistin that may initiate a positive feedback loop to increase effective intracellular levels of the antibiotic [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, we found that when combined with colistin it did exhibit an activity against drug resistant acinetobacter although this combination only produced a synergistic effect on 30% of our isolates, similarly a small number of studies demonstrated the same activity for AZM against Gram negative bacilli with no explanation or suggestion about the mechanism of synergy [31] [32]. Until Lin et al 2012 tested this combination in eukaryotic cell media and in vivo murine models of infection and concluded that AZM entry and activity is synergistically enhanced when the bacterial outer membrane was disrupted by colistin [11]. Buyck et al, 2012 demonstrated that a mutation of the oprM efflux pump system in P. aeruginosa lead to an increased AZM susceptibility, and on entry AZM reduced oprM gene expression and protein synthesis, further enhancing the entry of AZM in eukaryotic media and in synergy with colistin that may initiate a positive feedback loop to increase effective intracellular levels of the antibiotic [10].…”
Section: Discussionmentioning
confidence: 99%
“…Also azythromycin, the most commonly prescribed antibiotic in the U.S., is never recommended for clinical treatment of serious Gram negative infections because of poor or absent in vitro activity by standard in-vitro testing. However, antibacterial activity of azithromycin was found to be enhanced in tissue culture media vs. bacteriologic media, prompting closer examination of its interaction with drug resistant Gram negative bacilli [10] [11].…”
Section: Introductionmentioning
confidence: 99%
“…Healthcare-associated infections (HAI) are increasingly affecting public and private healthcare systems and raising not only hospital costs but also the morbidity and mortality rates of affected patients (1) (2) (3) . The bacterial genus Acinetobacter is recognized as a key HAI-causing pathogen that is associated with high mortality rates in hospital settings (2) (4) .…”
Section: Introductionmentioning
confidence: 99%
“…For example, MIC testing ignores possible interactions with host immune factors. Azithromycin, while lacking activity in standard susceptibility assays, possesses potent efficacy against multi-drug-resistant pathogens due to synergy with a host antimicrobial peptide [4]. On the other hand, many pathogens are documented to be highly susceptible in laboratory testing yet unresponsive in clinical therapy.…”
mentioning
confidence: 99%